Barriers to accessing support for mental health issues at university. Issue 8 (2nd August 2020) - Cage, Eilidh; Stock, Melissa; Sharpington, Alex; Pitman, Emma; Batchelor, Rachel
ABSTRACT: Student mental health is an issue of great concern for universities, with rising numbers of mental health problems being reported and students reporting issues with accessing support. The current study, using a participatory research framework, investigated the possible barriers preventing students from accessing support, in terms of help-seeking intentions and actual help-seeking behaviour. Three hundred and seventy-six current UK students completed a questionnaire which measured help-seeking and possible barriers including perceived public stigma, self-stigma, educational impact, disclosure, coping behaviours and current mental health symptoms. Findings indicated that self-stigma, in particular, was a barrier to accessing support. Disclosure, educational impact, previous diagnosis, suspected diagnosis and mental health symptoms also interacted with help-seeking. These findings have implications for universities in tackling the barriers preventing students accessing support for their mental health.